Patterns of antenal sensilla of Panstrongylus megistus from three Brazilian states - Villela, M. M. (2005)
The objective of the present study was to analyze and describe the phenotype of the antennal sensilla of Panstrongylus megistus, one of the epidemiologically most important species of triatomines in Brazil. Specimens from the Brazilian states of Goiás (GO), Minas Gerais (MG), and Rio Grande do Sul (RS) were compared, based on studies of four types of sensilla on three antennal segments: thick-walled trichoid (TK), thin-walled trichoid (TH), bristles (BR), and basiconica (BA). Discriminant analysis allowed the separation of the RS specimens from those of GO and MG. Multivariate discriminant analysis demonstrated that the sensilla of males differed from those of females, the variables with greatest weight being the BA of all three segments and the TK of flagellum 1. The basiconica sensilla were significantly more abundant in females, on all three segments. Antennal sensilla patterns also demonstrated significant differences among P. megistus specimens.